Logic Gone Wrong: A Reply to DeYoung, Howley & Theobald (1995) - Jon Wiles (Journal of Research in Rural Education, 1995)
When I initially read this manuscript as a reviewer, I was struck by the probability that the authors had wedded three different manuscripts to construct one. In manuscript one, a "straw man" is constructed by a misinterpretation of the history of the American middle school. In manuscript two, the middle school is blamed for the consolidation of rural schools in America. In manuscript three, this consolidation is credited with the demise of rural communities and some imaginary quality of life that previously existed. While there are many interesting ideas contained in the final article by DeYoung, Howley, and Theobald (1995), I find it to be poorly constructed and poorly reasoned.